2013
DOI: 10.2478/bvip-2013-0071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding genetically modified maize and soybean meal to sows on their reproductive traits, haematological indices and offspring performance

Abstract: The effect of Roundup Ready MON-40-3-2 soybean meal and Bt maize MON810 on sows performance and haematological indices, including parameters of erythrocytes, leukocytes, and trombocytes, as well as the piglets rearing indices were evaluated in the experiment carried out on 24 sows and their progeny. After mating sows were divided into groups: I -control, conventional soybean meal and conventional maize; II -genetically modified (GM) soybean meal and conventional maize; IIIconventional soybean meal and GM maize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…None were detected in the liver, spleen, or lymph nodes ( Chowdhury et al, 2003a , b ) indicating they were too large to be systemically absorbed from the GI tract. It has been suggested that transgenic nucleic acids and proteins from GM crops are handled in the gut like their conventional counterparts, with no evidence for systemic absorption of intact proteins or genes ( Światkiewicz et al, 2009; Walsh et al, 2012a , b ; Sieradzki et al, 2013 ). It is notable that farm animals generally have a much higher proportion of maize in their diets than humans; for example, in the case of broiler chickens, maize accounts for approximately 65% of their diet throughout their productive lifetime.…”
Section: Food Safety Assessment Of Cry Proteins Introduced Into mentioning
confidence: 99%
“…None were detected in the liver, spleen, or lymph nodes ( Chowdhury et al, 2003a , b ) indicating they were too large to be systemically absorbed from the GI tract. It has been suggested that transgenic nucleic acids and proteins from GM crops are handled in the gut like their conventional counterparts, with no evidence for systemic absorption of intact proteins or genes ( Światkiewicz et al, 2009; Walsh et al, 2012a , b ; Sieradzki et al, 2013 ). It is notable that farm animals generally have a much higher proportion of maize in their diets than humans; for example, in the case of broiler chickens, maize accounts for approximately 65% of their diet throughout their productive lifetime.…”
Section: Food Safety Assessment Of Cry Proteins Introduced Into mentioning
confidence: 99%
“…For example, GM corn, GM rice, GM soybean or purified plasmid DNA were introduced in the diets of rats, broilers, laying hens, pigs, piglets and calves. No instances of HGT of the introduced DNA to bacteria in the GIT was observed in these experiments ( Nemeth et al, 2004 ; Zhu et al, 2004 ; Deaville and Maddison, 2005 ; Calsamiglia et al, 2007 ; Wilcks and Jacobsen, 2010 ; Yonemochi et al, 2010 ; Walsh et al, 2011 ; Nordgård et al, 2012 ; Sieradzki et al, 2013 ; Świątkiewicz et al, 2013 ; Zhao et al, 2016 ).…”
Section: Pathway Considerations For Hgt From Gm Plantsmentioning
confidence: 69%
“…Although there is a comprehensive set of studies that confirm the absence of unintended effects and the nutritional equivalence of MON 810 maize to existing conventional hybrids, animal feeding studies should also be undertaken to provide further assurance of nutritional safety and value. There were no adverse effects of transgenic maize (Bt and Gt) on production indices, quality of pork (3, 23, 24), or meat of broiler chickens and laying hens (8, 25, 26, 27) uncovered in previous work. The obtained data indicated that transgenic DNA sequences from Bt maize are well digested in the gastrointestinal tract and are not transferred to animal tissues.…”
Section: Introductionmentioning
confidence: 83%
“…In an earlier 90-day safety assurance study with rats fed borer-protected maize, there were also no test article related changes in haematology parameters for the MON 810 maize fed animals (10). A series of Polish studies led the author to conclude that dietary GM maize did not affect the haematological parameters of pigs (23), Japanese quails (21), broiler chickens, or laying hens (25, 26). In the present investigation, blood creatinine concentration increased significantly in rats fed the GM diets.…”
Section: Discussionmentioning
confidence: 99%